Unlocking the Linguistic Wealth - Dilsel Zenginliğin Keşfi: A Call for Bilingual Education in the Republic of Türkiye - DiCarlo, Lisa; Hoş, Rabia (Bilingual Review / La Revista Bilingüe, 2025)
As Türkiye transitions from a sending to a receiving country for migrants, it faces new challenges and opportunities. The country has experienced a significant influx of migrants, notably Syrian refugees, which has strained its educational infrastructure while also presenting potential benefits. The current article examines the role of Türkiye’s linguistic landscape in integrating diverse migrant populations, considering its historical emphasis on a singular national identity. Türkiye’s evolving sociocultural context invites a reassessment of linguistic diversity policies, particularly for national minorities and immigrant communities. We propose a systematic bilingual education program to foster a bilingual future in Türkiye, advocating for educational policies that preserve minority languages and encourage linguistic pluralism in an increasingly interconnected global society. Türkiye göçmen gönderen bir ülkeden göçmen alan bir ülkeye dönüşürken yeni zorluklar ve fırsatlarla karşı karşıyadır. Ülke, özellikle Suriyeli mülteciler olmak üzere önemli bir göçmen akını yaşadı ve bu durum eğitim altyapısını zorlarken aynı zamanda potansiyel faydalar da sundu. Bu makale, Türkiye’nin dilsel manzarasının çeşitli göçmen nüfuslarını entegre etmedeki rolünü, tekil bir ulusal kimliğe olan tarihsel vurgusunu göz önünde bulundurarak incelemektedir. Türkiye’nin gelişen sosyokültürel bağlamı, özellikle ulusal azınlıklar ve göçmen topluluklar için dilsel çeşitlilik politikalarının yeniden değerlendirilmesini gerektirir. Bu makalede Türkiye’de çift dilli bir geleceği teşvik etmek için azınlık dillerini koruyan sistematik bir çift dilli eğitim programı öneriyoruz ve artan bir şekilde dilsel çoğulculuğu teşvik eden eğitim politikalarını savunuyoruz.
Keywords: dept.grad

Empowering Newcomer Students with Inconsistent/Interrupted Formal Education (SIFE) in Secondary Schools: Urgent Call for Comprehensive Literacy Support - Hos, Rabia; Sari, Gulhan (The Literacy and Urban Schools Journal, 2025)
Keywords: dept.grad; peer-reviewed

Racial Literacy Development of Pre-Service Teachers: Exploring Race, Culture, Language, and Privilege through TESOL Course Work - Hos, Rabia; Seloni, Lisya (Preparing Antiracist ESOL Professionals: Linguistic Equity for Multilingual Learners, 2025)
This chapter presents a multi-institutional study that explores 38 pre-service English to Speakers of Other Languages (ESOL) teachers’ identity development in
Keywords: dept.grad

Combating misinformation in the COVID-19 vaccine supply chain - DuBois, D.; Hoş, Rabia; Ashraf, Muhammad; Yalcin, Mehmet (Academy of Management Proceedings, 2025)
Keywords: Conceptual framework; Conceptual model; Misinformation; Stakeholder; Stakeholder engagement; Supply chain; Supply chain management; dept.grad

Bridging Borders: Teacher Perspectives on Refugee Students’ Schooling in Germany and the U.S. - Beck, Abby; Becker, Carmen; Hoş, Rabia (Multicultural Perspectives, 2025)
Keywords: Bridging (networking); Citizenship; Immigration; Qualitative research; Refugee; Teacher education; dept.grad

Syria, English in - Hadid, Alia; Hos, Rabia (The Wiley Blackwell Encyclopedia of World Englishes, 2025)
To gain a full perspective about English in Syria, it is necessary to focus on English learning in the past and present. The focus of the learning and teaching of the English language in Syria prior to 2011 consisted of various factors such as length of exposure to language, teacher preparation, qualifications, cross-linguistic transfer, and textbooks. The interruptions in schooling, brain drain, and depletion of resources were additional factors that influenced the learning and teaching of English in Syria in the post-2011 era. The entry concludes with a proposal that conscientious efforts are needed to enhance the teaching of English in Syria.
Keywords: Computer science; English language teaching; English learning; Geography; History; Linguistics; Middle East; Philosophy; Syria; Syrian refugees; dept.grad; language education; teacher training

Empathy in action: nurturing sustainable educational change through Nel Noddings' ethics of care - Hadid, Alia; Hos, Rabia; Hauber-Özer, Melissa (Journal of Ethnic and Cultural Studies, 2025)
This introduction synthesizes the research presented by the contributors to this special issue to explore sustainable educational practices for refugees. A common thread across the articles is that they share components of Nel Noddings’ ethics of care framework, which emphasizes establishing welcoming, nurturing, and supportive environments that enable refugees to build meaningful relationships while honoring their cultural identities. We recommend action steps gleaned from the 11 papers in this issue that call for the concerted efforts of all those involved. Central to this vision are teachers, who serve as the backbone of the education system; however, to fulfill this role, they must be equipped with the necessary resources and skills to foster culturally responsive educational environments that emphasize students’ identities and provide equitable learning. This introduction underscores the importance of holistic and relational approaches as foundational to achieving sustainable educational equity for refugee learners.
Keywords: Community; dept.grad; empathy; empowerment; equity; inclusive; peer-reviewed